MOODLE AS AN EXTENSIVE READING MECHANISM: A STUDY TO FACILITATE EXTENSIVE READING IN AN OMANI EFL CONTEXT - Al Zeidi, Jawaher; Al Quraini, Buthaina (PEOPLE: International Journal of Social Sciences, 2019)
Extensive Reading (ER) in the English as Foreign Language (EFL) field is of paramount importance for students’ academic success. For this reason, innovative teaching and testing mechanisms must be applied in extensive reading programs in order to enhance students’ language learning. This paper reports on the results of a mixed methods case study of ninety-eight Level 2 EFL foundation students at Middle East College in the Sultanate of Oman. The study explored the effectiveness of a MOODLE extensive reading program in assessing students’ extensive reading skills. The MOODLE program was utilized to measure students’ understanding of the graded stories and to track their reading progress. Results of the quantitative data analysis indicated a substantial improvement in students’ reading comprehension, number of attempts, motivation to read, and comfort, as well as a preference to the novel assessment method. Although both the standard and MOODLE assessment methods demonstrated significant students’ gains and the success of the ER program in the context of study, the MOODLE program enhanced these gains considerably.